2014
DOI: 10.7150/ijbs.8868
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Hypothermia Is Neuroprotective in an in vitro Model of Ischemic Stroke

Abstract: Objective: To investigate whether the intermittent hypothermia (IH) protects neurons against ischemic insult and the potential molecular targets using an in vitro ischemic model of oxygen glucose deprivation (OGD).Methods: Fetal rat cortical neurons isolated from Day E18 rat embryos were subjected to 90-min OGD and hypothermia treatments during reoxygenation before examining the changes in microscopic morphology, cell viability, microtubule- associated protein 2 (MAP-2) release, intracellular pH value and calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…MAP-2, a protein expressed primarily in neuronal dendrites, is critical for numerous microtubule-related processes, including microtubule assembly, stabilization and cross-linking (26). MAP-2 deficiency following ischemic stroke has been documented in previous studies (27,28). In the present study, decreased MAP-2 immunofluorescence activity was observed in MCAO model rats, indicating MAP-2 defect in ischemic stroke.…”
Section: Discussionsupporting
confidence: 72%
“…MAP-2, a protein expressed primarily in neuronal dendrites, is critical for numerous microtubule-related processes, including microtubule assembly, stabilization and cross-linking (26). MAP-2 deficiency following ischemic stroke has been documented in previous studies (27,28). In the present study, decreased MAP-2 immunofluorescence activity was observed in MCAO model rats, indicating MAP-2 defect in ischemic stroke.…”
Section: Discussionsupporting
confidence: 72%
“…Amongst these, an increased expression of the protective GRP78 has been identified, and decreased expression of proapoptotic factor CHOP and, thereby, a reduction in apoptosis [ 19 , 20 ]. Furthermore, hypothermia is known to induce neuroprotection both in vivo [ 19 , 20 ] and in vitro [ 21 ]. Ero1-α has been identified as a CHOP target; however, contradictory evidence on signaling molecules leading to activation of the two isoforms Ero1-α/β exists [ 15 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The primary neurons were cultured as previously described (16) with some modifications. Briefly, the cerebral cortex from rat no more than 7 d after birth was collected and cut into pieces as small as possible.…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%